Histopathological differentiation and incidence of soft tissue tumors: study of 140 cases - Dr. Yogita kumara Manilal Patel; Dr. Hetalkumari Kishorbhai Tandel (Tropical Journal of Pathology and Microbiology, 2017)
Background: The incidence of soft tissue tumors, especially the frequency of benign tumors relative to malignant ones, is never determined accurately. The fact that many benign tumors, such as lipomas and hemangiomas, do not undergo biopsy makes direct application of data from most hospital series invalid for the general population. Histologic grade represents the most important Prognostic factor for all soft tissue sarcomas, strongly associated with the advent of metastasis and patients survival.Objectives: the objective of the study was to find occurrence of soft tissue tumor and analyse various type and sub types of soft tissue tumors.Methodology: a prospective study carried out at tertiary care teaching hospital. The operated specimens or biopsy material of soft tissue tumors received were studied in detailed by department of Histopathology. Histological diagnosis was achieved either by performing incisional or trucut needle biopsy and/or reviewing the slides when patient underwent biopsy elsewhere.Observations: The incidence were high in the age group of 31 to 40 years (36 cases, 25%), followed by 21 to 30 years (24 Cases, 17.1%) and 41 to 50 (21 Cases, 15%) years. However the malignant tumor incidence was high at age of 51 to 60 years of age. Region wise involvement shows soft tissue tumors were found in head and neck region (29.2%), followed by genital region (25.7%) and upper limb (15.8%). Type wise distribution was lipomatous (28.5%), followed by smooth muscle tumor (21.5%), peripheral nerve sheath tumor (17.9%), Tumor of blood and lymph vessels (17.1%),Conclusion: benign soft tissue tumor are much common than the malignant tumors. Among benign tumors lipomatous tumors are common followed by smooth muscle tumor and other tumors.